2019
DOI: 10.1186/s12891-019-2958-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary selenium intake and the prevalence of osteoporosis: a cross-sectional study

Abstract: ObjectiveTo examine the correlation between dietary selenium (Se) intake and the prevalence of osteoporosis (OP) in the general middle-aged and older population in China.MethodsData for analyses were collected from a population based cross-sectional study performed at the Xiangya Hospital Health Management Centre. Dietary Se intake was evaluated using a validated semi-quantitative food frequency questionnaire. OP was diagnosed on the basis of bone mineral density scans using a compact radiographic absorptiomet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 59 publications
(64 reference statements)
3
39
0
Order By: Relevance
“…A study showed a negative correlation between the amount of selenium intake and osteoporosis [ 122 ]. On the other hand, the serum selenoprotein level correlated positively with total BMD, and the serum selenium level with the total and femoral neck BMD in aging men from Europe.…”
Section: Microelements and Bone Mineral Density In Ibdmentioning
confidence: 99%
“…A study showed a negative correlation between the amount of selenium intake and osteoporosis [ 122 ]. On the other hand, the serum selenoprotein level correlated positively with total BMD, and the serum selenium level with the total and femoral neck BMD in aging men from Europe.…”
Section: Microelements and Bone Mineral Density In Ibdmentioning
confidence: 99%
“…After reviewing the full-texts of the remaining 774 articles, 3 studies were excluded due to sample size smaller than 100, 2 studies were excluded due to repeated publications, 750 studies were excluded as diabetes mellitus was not investigated, and 5 studies were excluded because no information is given about BMD [ 28 32 ]. Finally, 14 relevant studies were included in this systematic review [ 33 46 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These 14 case-controlled studies included 24,340 participants, and the sample size ranged from 255 to 6267. Five studies were conducted in China [ 33 , 34 , 39 , 44 , 46 ], two in Korea [ 43 , 45 ], two in Jordan [ 35 , 41 ], and the remaining in other countries. Most of the low bone density patients underwent dual-energy X-ray absorptiometry.…”
Section: Resultsmentioning
confidence: 99%
“…Higher selenium status is associated with BMD in men in the Netherlands. 22 Higher dietary selenium intake is associated with lower hip fracture risk in older adults in the USA 23 and higher BMD in middle-aged and older adults in China 46 and Europe. 14,22 However, there was no association with BMD in postmenopausal Turkish women.…”
Section: Resultsmentioning
confidence: 99%